Metabolic engineering of the carotenoid biosynthetic pathway toward a specific and sensitive inorganic mercury biosensor. Issue 55 (16th December 2022) - Hui, Chang-ye; Hu, Shun-yu; Li, Li-mei; Yun, Jian-pei; Zhang, Yan-fang; Yi, Juan; Zhang, Nai-xing; Guo, Yan
Abstract : Genetically controlled carotenoid biosynthesis produces a specific and sensitive biosensor for inorganic mercury. Abstract : The toxicity of mercury (Hg) mainly depends on its form. Whole-cell biosensors respond selectively to toxic Hg(ii ), efficiently transformed by environmental microbes into methylmercury, a highly toxic form that builds up in aquatic animals. Metabolically engineered Escherichia coli ( E. coli ) have successfully produced rainbow colorants. By de novo reconstruction of the carotenoid synthetic pathway, the Hg(ii )-responsive production of lycopene and β-carotene enabled programmed E. coli to potentially become an optical biosensor for the qualitative and quantitative detection of ecotoxic Hg(ii ). The red color of the lycopene-based biosensor cell pellet was visible upon exposure to 49 nM Hg(ii ) and above. The orange β-carotene-based biosensor responded to a simple colorimetric assay as low as 12 nM Hg(ii ). A linear response was observed at Hg(ii ) concentrations ranging from 12 to 195 nM. Importantly, high specificity and good anti-interference capability suggested that metabolic engineering of the carotenoid biosynthesis was an alternative to developing a visual platform for the rapid analysis of the concentration and toxicity of Hg(ii ) in environmentally polluted water.